"This worry machine": The impact of executive orders on ELL teachers. Issue 3 (29th August 2018) - Petrie, Gina Mikel; Darragh, Janine J.
Abstract : This research study sought to answer the question: What are the immediate emotional impacts of recent executive orders on teachers of English language learners in the United States? Eight teachers of K–12 English language learners (ELLs) were interviewed in the weeks following the signing of Executive Orders 13, 767 and 13, 769 in 2017, which attempted to limit refugee resettlement and immigration. Through thematic analysis of the data, it was found that the executive orders set a process in motion in which ELLs were encouraged to feel fear. Teachers experienced emotion labor (Hochschild, 1983 ) as they attempted to buffer the messages of fear and mitigation of that emotion labor when they felt support from colleagues. The study concludes that teachers and school leaders should address ELLs' experiences of fear arising from a context of anti‐immigrant sentiment and demonstrate care for those teachers who most closely work with them.